Parent’s Preferences in the Future Orientation of Girl’s Education (Ethnographic Studies Among Fisherman Families in Muncar Banyuwangi) - Zombieta Bening Tatas Kamantyan; Vina Salviana Darvina Soedarwo; Rachmad K. Dwi Susilo (Universitas Muhammadiyah Malang, 2021)
Future orientation is a design, plan, and view of an individual in the context of his education in the future which aims to direct himself to behave in accordance with the expected future. The future orientation of girls' education is shaped by parents through a preference. Preference is a choice or decision that must be prioritized, prioritized, and prioritized. Parents' preferences in the future orientation of girls' education, do not want their daughters to go to college. The cultural system of society influences the construction of a person's thinking so that it forms a preference within the scope of the family which is the smallest institution in society. Among fishermen's families, the level of education can be said to be lower because the struggle to meet the daily needs of a fisherman is at sea facing big waves, uncertain weather, and income which is determined by the number of fish caught makes a problem that is hampering the fulfillment of educational needs. child. This study aims to describe and explain the forms and factors that influence parental preferences in the future orientation of girls' education among fishing families in Muncar District, Banyuwangi Regency. This research chooses a qualitative approach with an ethnographic research type that aims to understand the indigenous people's point of view regarding the relationship with life, namely studying society and learning from society. Data collection techniques used participant observation, interviews, and document studies. The results of the research data obtained that preferences are divided into several forms, while the influencing factors are the family economy, community culture, and the mindset of parents. These forms and factors are collaborated with the concept of patriarchal culture.